Perbandingan Persepsi Mahasiswa Pendidikan Matematika Terhadap Pembelajaran Daring, Luring dan Blended Learning Pasca Pandemi Covid-19 - Irajuana Haidar; Jahring Jahring (Universitas Muhammadiyah Semarang, 2022)
This study aims to compare student perceptions of online, offline, and blended learning involving 28 students from the 2018 batch of Mathematics Education Study Program, Faculty of Teacher Training and Education, Sembilanbelas November Kolaka University as research subjects. The data were collected by non-test using a questionnaire instrument of student perceptions including online, offline, and blended learning as many as 23 statement items followed by interviews related to student perceptions. The results of this study indicate that the mean student perception of learning is positive with the following details: (1) the mean percentage of student perceptions of online learning is 77.92%; (2) the mean percentage of students' perceptions of offline learning (face-to-face) is 82.86%; and (3) the mean percentage of students' perceptions of blended learning is 73.98%.